The Impact of a Coronavirus Epidemic on China’s Public Debt Ratio Growth - Török, László (International Journal of Engineering and Management Sciences, 2020)
Public opinion in the economic profession is strongly preoccupied with the expected negative economic effects of the coronavirus epidemic. Among the consequences, special attention is paid to the increase in the gross debt of the states. Indeed, based on conventional economic knowledge, it is clear to everyone that the economic downturn and the increase in government sector expenditure will directly lead to a sharp rise in government debt. The study aims to predict an increase in China’s government debt ratio using a macroeconomic model. The study will quantify the rate of increase in China’s public debt based on four theoretically possible scenarios for the course of the coronavirus epidemic. I am aware that it is difficult to apply conventional economic knowledge to China’s state-capitalist system. This is explained by the fact that the theories of the socialist economic model do not apply to China either. At the same time, the functioning of China’s economy is closer to that of market-based economies, but the country’s structure as a whole cannot be integrated into this framework either. But models describing the economic development of developing national economies cannot be applied to the country either. Nonetheless, I attempt to use conventional economic economics to attempt to quantify the impact of the coronavirus epidemic on China’s sovereign debt ratio. China’s public debt growth rates calculated under different outbreak scenarios are different, but none show an increase that would call into question the financing of China’s public debt.